Isolasi Bakteri Pendegradasi Hidrokarbon di Tanah Tercemar Lokasi Perbengkelan Otomotif - Hezi Yolantika; Periadnadi Periadnadi; Nurmiati Nurmiati (Universitas Andalas, 2015)
The research related to Isolation of the Hydrocarbon Degrading Bacteria in the Contaminated Soil of the Automotive Workshop was conducted from May to October 2014 at Laboratory of Microbiology, Biology Department, Faculty of Mathematics and Natural Sciences, Andalas University. The aimed of this study was to find the bacteria able to degradate the hydrocarbon from the lubricating oil contaminated soil and to descripe characterization of isolates. This study used a survey method in isolation and characterization of hydrocarbon degrading bacteria. The result obtained that the bacteria able to degradate the hydrocarbon from the lubricating oil contaminated soil about 39.02% (1.6x105 cfu/g). Five isolates were found (BTTO1, BTTO2, BTTO3, BTTO4 and BTTO5) has a rod shaped, Gram-negative, motile and positive catalase.